Towards Information Systems Development Approach for Individual Information Systems - Santa, Mijalche (Faculty of Economics & Business, University of Zagreb, 2023)
In the ubiquitous information society era, individual information systems have emerged as a potential game-changer for understanding information systems development (ISD). These systems are highly mutable, ad hoc, and subjective in scope and methodology, which contrasts with traditional rational ISD approaches. This paper aims to explore the practices used for developing individual information systems and their implications for ISD. Individual information systems are activity systems where individuals, based on their idiosyncratic needs and preferences, utilize information, technology, and other resources to produce informational products and services for themselves or others. These practices are under-researched, and understanding how individuals overcome ISD problems can provide valuable insights into improving ISD practices. The methodology employed in this study is design ethnography, which involves active intervention and the researcher’s creation of the IT artifact. This approach allows for an in-depth exploration of individual practices in developing information systems. We focus on the author’s personal ethnographic experiences in developing an individual information system for writing. We propose the concept of “nomadic information systems development” as a result of our findings. Unlike conventional rational ISD, nomadic ISD involves users engaging in do-it-yourself practices that lead to diffused translation of solutions, ultimately creating individual information systems. There are practical implications to understanding nomadic ISD. Individuals with little to no programming or system development knowledge are building their systems, making them more susceptible to security threats, data compromise, privacy violations, and more. Identifying and leveraging these practices can help improve information systems development and security. This research offers a deeper understanding of the development of individual information systems by exploring the practices employed and proposing the nomadic information systems development approach. This approach can potentially impact the way information systems are developed in the future, particularly in the context of the ubiquitous information society. By examining these practices and their consequences for ISD, we aim to contribute to the ongoing academic and practical discourse surrounding information systems development.
Keywords: individual information systems, information systems development, design ethnography, ubiquitous information society, do-it-yourself practices